2010
DOI: 10.1080/15548732.2010.496077
|View full text |Cite
|
Sign up to set email alerts
|

Learning How to Dance with the Public Child Welfare System: Mexican Parents' Efforts to Exercise Their Voice

Abstract: The purpose of this article is to understand how Mexican parents' perceive their voices (their concerns, dissatisfaction, and opinions) as integrated in child welfare cases and what factors hinder or promote this process. The focus is on parents' interactions with their child welfare worker during routine monthly home visits. Nineteen parents, with a history of immigration, participated in in-depth interviews for this qualitative study. Grounded theory methods were used to complete the content analysis. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…As Brown (2006) suggests, this approach to child welfare intervention will also lead parents to conceal their struggles to avoid or prevent child welfare intervention. A similar lack of knowledge was found among Mexican and other Latino immigrant families in the United States (Ayon et al, 2010). Service users expressed the need for more information about how the system works and more practical help in gaining employment, earning a steady income, and obtaining affordable housing, education, and subsidized child care.…”
Section: Misinformation or Lack Of Informationmentioning
confidence: 76%
See 1 more Smart Citation
“…As Brown (2006) suggests, this approach to child welfare intervention will also lead parents to conceal their struggles to avoid or prevent child welfare intervention. A similar lack of knowledge was found among Mexican and other Latino immigrant families in the United States (Ayon et al, 2010). Service users expressed the need for more information about how the system works and more practical help in gaining employment, earning a steady income, and obtaining affordable housing, education, and subsidized child care.…”
Section: Misinformation or Lack Of Informationmentioning
confidence: 76%
“…A 2006 government study found a decline in these rates for both Black (32%) and White (40%) children, but the overrepresentation of African American children remains (Roberts, 2002;United States Government Accountability Office, 2007). In the past 10 years, Latino children and families have also entered the child welfare system in significant numbers (Ayon, Aisenberg, & Erera, 2010;Garcia, 2009;Hines, Lemon, Wyatt, & Merdinger, 2004;Rivera, 2002). While they are underrepresented at the national level, they are overrepresented in some states and counties (Dougherty, 2003).…”
Section: Racialization Of Child Welfare Servicesmentioning
confidence: 98%
“…The child welfare system in both countries is perceived by parents as being inflexible, punitive, frightening, and powerful even with the presence of cooperative workerÁparent relationships (Altman, 2008a;2008b;Ayon, Aisenberg, & Erera, 2010;Bundy-Fazioli, BriarLawson, & Hardiman, 2009;CCfE, 2010;Corby, Millar, & Young, 1996;Davies, 2011;Ghaffar et al, 2011;Sykes, 2011). These perceptions are likely to be of even greater intensity for those subgroups of parents experiencing broader forms of oppression such as women, ethnic minorities, and those living in poverty.…”
Section: Problem Definition and Parental Reluctancementioning
confidence: 90%
“…Concerns regarding the provision of relevant services for minority immigrant parents in the child welfare system in Western countries have been well documented (Maiter et al 2009). Overall, immigrant parents have been identified as having little opportunity to voice their concerns, opinions and satisfaction, or lack thereof, with the system because of a number of factors, including lack of knowledge of the system, immigration status, fear of losing their children and perceptions of how their concerns are received by workers (Ayón et al 2010). Furthermore, language barriers have increasingly been identified as contributing to service concerns in the child welfare systems (Maiter & Stalker 2011;Pomeroy & Nonaka 2013).…”
Section: Introductionmentioning
confidence: 99%